Characterization of Swallowing Sounds with the Use of Sonar Doppler in Full-Term and Preterm Newborns - Lagos,Hellen Nataly Correia (2013)
Introduction  Technological advances have provided a large variety of instruments to view the swallowing event, aiding in the evaluation, diagnosis, and monitoring of disturbances. These advances include electromyography of the surface, dynamic video fluoroscopy, and most recently sonar Doppler. Objective  To characterize swallowing sounds in typical children through the use of sonar Doppler. Method  Thirty newborns participated in this prospective study. All newborns received breast milk through either their mother's breasts or bottles during data collection. The newborns were placed in either right lateral or left lateral positions when given breast milk through their mother's breasts and in a sitting position when given a bottle. There were five variables measured: initial frequency of sound wave (FoI), frequency of the first peak of the sound wave (FoP1), frequency of the second peak of the sound wave (FoP2), initial intensity and final sound wave (II and IF), and swallowing length (T), the time elapsed from the beginning until the end of the analyzed acoustic signal measured by the audio signal, in seconds. Results  The values obtained in the initial frequency of the babies had a mean of 850 Hz. In terms of frequency of first peak, only three presented with a subtle peak, which was due to the elevated larynx position. Conclusion  The use of sonar Doppler as a complementary exam for clinical evaluations is of upmost importance because it is nonintrusive and painless, and it is not necessary to place patients in a special room or expose them to radiation.